2011
DOI: 10.1007/s00401-011-0892-1
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E level and cholesterol are associated with reduced synaptic amyloid beta in Alzheimer’s disease and apoE TR mouse cortex

Abstract: The apolipoprotein E4 allele (APOE4) contributes to Alzheimer’s disease (AD) risk and APOE2 is protective, but the relevant cellular mechanisms are unknown. We have used flow cytometry analysis to measure apolipoprotein E (apoE) and amyloid beta peptide (Aβ) levels in large populations of synaptic terminals from AD and aged cognitively normal controls, and demonstrate that modest but significant increases in soluble apoE levels accompany elevated Aβ in AD cortical synapses and in an APP/PS1 rat model of AD. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 75 publications
8
32
0
Order By: Relevance
“…People who carry APOE ε4 allele have an increased risk of developing AD, while APOE ε2 carriers are protected from the disease (Deelen et al ., 2011). The level of soluble ApoE protein increases both in patients with AD and in APP/PS1 rat model of AD (Arold et al ., 2012). It plays an important role in Aβ aggregation and fibril formation (Wisniewski et al ., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…People who carry APOE ε4 allele have an increased risk of developing AD, while APOE ε2 carriers are protected from the disease (Deelen et al ., 2011). The level of soluble ApoE protein increases both in patients with AD and in APP/PS1 rat model of AD (Arold et al ., 2012). It plays an important role in Aβ aggregation and fibril formation (Wisniewski et al ., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…At the synapse, as with the whole brain, apoE/A␤ appears to be present as an insoluble and soluble form. IHC co-localization of apoE and A␤ at the synapse is a measure of primarily insoluble apoE/A␤ (35,36), and data demonstrate insoluble apoE/A␤ appears to form preferentially with apoE4 compared with apoE3 (36). Previous results have shown that the detergent and guanidine extraction pattern of mouse apoE parallels that of A␤42 in 5ϫFAD mice (5), and the proportion of apoE/A␤ in insoluble fractions was increased in AD synaptosomes compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE/A␤ complex has been detected in the soluble fraction of human brain (33) and in human cerebrospinal fluid (CSF) (30,34), although the data were primarily produced using Western analysis of SDS-PAGE. By IHC, apoE also co-localizes with A␤ at the synapse (35), and insoluble apoE/A␤ complexes appear to form preferentially with apoE4 compared with apoE3 (36). However, the effect of the APOE genotype on soluble synaptic apoE/A␤ levels remains unclear (37)(38)(39)(40).…”
mentioning
confidence: 99%
“…Human ApoE3 and ApoE4 transgenic mice (driven by the human APOE promoter) were made in the ApoE-ko background (Xu et al, 1996;Sullivan et al, 1997;Holtzman et al, 1999;Teter et al, 2002;Arold et al, 2012). These mice show equivalent levels of ApoE expression in astrocytes, microglia, and neurons and maintain the human pattern of regulation and regional expression (Xu et al, 1996).…”
Section: Methodsmentioning
confidence: 99%